MATERIALS FOR A REVISION OF LAURACEAE V - A.J.G.H. KOSTERMANS (BRIN Publishing (Penerbit BRIN), 1988)
New species are described in Cinnamomum (12), Cryptocarya (8), Endiandra (2) and Litsea (1). New combinations are proposed in Actino-daphne (1), Cinnamomum (20), Endiandra (1), Litsea (1), Neolitsea (1). Moreover new names are proposed in Cryptocarya (1) and Litsea (7). The generic name Kubitzkia van der Werff is considered invalid and numerous species are reduced to synonymy for the first time.